Dosimetric comparisons of carbon ion treatment plans for 1D and 2D ripple filters with variable thicknesses. (20th May 2016) - Ringbæk, Toke Printz; Weber, Uli; Santiago, Alina; Simeonov, Yuri; Fritz, Peter; Krämer, Michael; Wittig, Andrea; Bassler, Niels; Engenhart-Cabillic, Rita; Zink, Klemens
Abstract: A ripple filter (RiFi)—also called mini-ridge filter—is a passive energy modulator used in particle beam treatments that broadens the Bragg peak (BP) as a function of its maximum thickness. The number of different energies requested from the accelerator can thus be reduced, which significantly reduces the treatment time. A new second generation RiFi with 2D groove shapes was developed using rapid prototyping, which optimizes the beam-modulating material and enables RiFi thicknesses of up to 6 mm. Carbon ion treatment plans were calculated using the standard 1D 3 mm thick RiFi and the new 4 and 6 mm 2D RiFis for spherical planning target volumes (PTVs) in water, eight stage I non-small cell lung cancer cases, four skull base chordoma cases and three prostate cancer cases. TRiP98 was used for treatment planning with facility-specific base data calculated with the Monte Carlo code SHIELD-HIT12A. Dose-volume-histograms, spatial dose distributions and dosimetric indexes were used for plan evaluation. Plan homogeneity and conformity of thinner RiFis were slightly superior to thicker RiFis but satisfactory results were obtained for all RiFis investigated. For the 6 mm RiFi, fine structures in the dose distribution caused by the larger energy steps were observed at the PTV edges, in particular for superficial and/or very small PTVs but performances for all RiFis increased with penetration depth due to straggling and scattering effects. Plans with the new RiFi design yielded for the studied cases comparable dosimetric results to the standard RiFi while the 4 and 6 mm RiFis lowered the irradiation time by 25–30% and 45–49%, respectively.